أهمية حوكمة الأمن السيبراني لضمان تحول رقمي آمن للخدمة العمومية في الجزائر - زمورة, جمال; بن عيسى, ليلى (جامعة الوادي - University of Eloued, 2022)
في ظل تحول الجزائر إلى الحكومة الإلكترونية من خلال التحول الرقمي التدريجي للخدمات العمومية، وما يصاحبه من انفتاح على الفضاء السيبراني، كان لزاما الأخذ بعين الاعتبار لمتغير الأمن السيبراني الذي يشكل الهاجس الأكبر للدول والشركات الكبرى. إن تبني برامج وإستراتيجيات واضحة وشفافة لحوكمة الأمن السيبراني ضرورة حتمية تمليه المصلحة العليا للوطن ترتكز على نماذج وأطر عملية يمكن الوثوق بفعاليتها، خاصة وأن نقائص ملحوظة تشوب المجهودات المبذولة مقارنة مع المعايير والتصنيفات الدولية المعتمدة. إن الاستفادة من تجارب الدول الرائدة في هذا الميدان إقليميا ودوليا، مع تدعيم الإجراءات التنظيمية والتحكم في التقنيات المتطورة في ميدان الأمن السيبراني بالاعتماد على الموارد البشرية ذات الكفاءة والمهارة العالية، لتحقيق الأمن السيبراني للوطن وللخدمات العمومية الرقمية الموجهة للمستخدمين. At the dawn of Algeria’s transformation to e-government through the gradual digital transformation of public services, and the attendant openness to cyberspace, it was necessary to take into account the cybersecurity variable that is the greatest concern for countries and large companies. the adoption of clear and transparent programs and strategies for cybersecurity governance is imperative, dictated by the supreme interest of the country based on practical models and frameworks whose effectiveness will trust, especially since there are noticeable shortcomings in the efforts made compared to the approved international standards and classifications. Benefiting from the experiences of the leading countries in this field regionally and internationally, while strengthening regulatory rules and controlling advanced technologies in the field of cybersecurity, relying on highly qualified and skilled human resources, to ensure cybersecurity for the country and for digital public services directed to users in particular.
Importance of cybersecurity governance for ensuring a secure digital transformation of the public services in Algeria
مقال
Keywords: الأمن السيبراني ; حوكمة الأمن السيبراني ; التحول الرقمي ; الخدمة العمومية